Distribution characteristics of MTHFR C677T gene polymorphism in Han nationality and women of childbearing age in 8 regions of Shaanxi province and a comparative analysis with other regions in China - Chen, Ting; Song, Fei; Sun, Jinyao; Yi, Jing; Ma, Wenbing (Frontiers in Genetics, 2025)
ObjectiveTo analyze the distribution characteristics of MTHFR C677T gene polymorphism in Shaanxi Province, thereby providing a genetic basis for folic acid supplementation strategies and the reduction of adverse pregnancy outcomes among reproductive-aged women in this region.MethodsA total of 8,779 Han women of childbearing age were recruited from the First Affiliated Hospital of Xi’an Jiaotong University and Baoji Maternal and Child Health Hospital for MTHFR C677T genotyping. The genotype and allele distribution patterns across eight regions in Shaanxi were systematically compared with domestic and international populations.ResultsIn the Shaanxi Province, the genotype frequencies of MTHFR C677T polymorphism ranked as follows: CT (48.49%), TT (29.22%), and CC (22.29%). Allelic frequencies were 46.54% (C) and 53.46% (T). Significant regional variations in MTHFR C677T genotype frequencies (P < 0.05) were observed among the eight prefectures of Shaanxi. Notably, the Xi’an region exhibited distinct genotype and allele distribution patterns compared to most reported Chinese populations (P < 0.05).ConclusionThere are significant interregional differences in the distribution of MTHFR C677T genotypes and alleles across Shaanxi Province. The genetic polymorphism pattern of MTHFR C677T genotypes and allele frequencies in Han women of reproductive age in Xi’an is significantly distinct from that in many other regions.